Aliança terapêutica estabelecida entre o fisioterapeuta e paciente com base na teoria do apego e regulação emocional - Alcântara, Irys Arielly Bernardo de (2023)
Introduction: The therapeutic alliance and attachment are predetermining factors for interaction between therapist and patient. This relationship can be interfered with by emotional regulation. In the presence of dysregulation, strategies such as suppression and reevaluation are valid. There is evidence that insecure attachment leads to weaker therapeutic alliances, but there has been less emphasis on the role of the physiotherapist as a facilitator or hinderer of the relationship with their patients. Objective: Investigate possible relationships between type of attachment, emotional regulation and therapeutic alliance. Methods: This research is characterized as a cross-sectional and correlational ex post facto type, with a sample of 32 physiotherapists (15 women and 17 men) with an average age of 30.5 years, answering the questionnaires online through a link made available to all of them completed the research that used the following instruments: therapeutic alliance assessment (Working Alliance Inventory), childhood attachment scale (Parental Bonding Instrument-PBI), Difficulties in Emotional Regulation Scale (DERS), Depression scale , Anxiety and Stress (DASS-21), Emotional Regulation Questionnaire (ERQ). Results: Emotionally dysregulated individuals are correlated with greater symptoms of anxiety, depression and stress, (R=0.516; R=0.320; R=0.471), the lower the overprotective attachment, the greater the intensity of the alliance relationship in terms of the bond, task aspect and objective (R=-0.229; - R=0.313; R=-0.404). Simple linear regression demonstrated a significant association of overprotective attachment as a form of therapeutic alliance predictions (β=58.301), but not significant for caring attachment. Difficulty in emotional regulation predicts the corresponding alliance (β=64,063). Discussion: It is suggested that individuals with overprotective attachment to emotionally dysregulated individuals present anxiety, depression and stress, in addition to regulation strategies, suppression and therapeutic alliances plus fights. Conclusion: Lower levels of overprotective attachment lead to stronger therapeutic alliance objectives and tasks, in order to develop their skills with a certain number of patients resort to emotional suppression strategies, with time of professional experience in favor of the objectives proposed in stronger therapeutic alliances.